Secrets of power negotiating : - Dawson, Roger (Career Press, 2001)
Secrets of Power Negotiating covers every aspect of the negotiating process with practical, proven advice: from beginning steps to critical final moves, how to recognize unethical tactics, key principles to the Power Negotiating strategy, why money is not as important as everyone thinks, negotiating pressure points, understanding the other party and gaining the upper hand, and analyses of different negotiating styles.